Peningkatan Motorik Halus dan Partisipasi Aktif Anak melalui Pembelajaran Kontekstual Berbasis Sentra dengan Media Daur Ulang - Tazqia Lailatuzzahra; Meysa Helvina D; Melinda A. S.; Neng Hani; Maghfira Hikmatul Adha (Universitas Pakuan, 2026)
Improvement of Fine Motor and Active Participation of Children through Center-Based Contextual Learning with Recycled Media Low fine motor skills and child engagement in preparation center activities are main problems in early childhood education. This study aimed to improve fine motor skills and engagement of Group B children through contextual learning based on the preparation center using recycled materials. The method used was Classroom Action Research with the Kemmis and McTaggart model, conducted in three cycles of planning, action, observation, and reflection. Subjects were 15 children aged 5-6 years at PAUD Mutiara Bunda. Data were collected through observation, interviews, and documentation using validated observation sheets for fine motor skills and child engagement. Data were analyzed using qualitative and quantitative descriptive analysis. Results showed fine motor skills increased from an average score of 1.75 (Developing) in pre-action to 3.45 (Very Well Developed) in Cycle III, with 86.7% completion rate. Child engagement also increased from 2.05 (Starting to Develop) to 3.70 (Very Well Developed), with 93.3% completion rate. The study concludes that contextual learning based on the preparation center using recycled materials is effective in improving fine motor skills and child engagement. The implication is the importance of teachers utilizing recycled materials as innovative, affordable, and sustainable learning media in early childhood education.